Macroeconomic Determinants of Financial Failure Risk in Airlines - ALICI, Abdulkadir (Journal of Aviation, 2023)
The objective of this study is to identify the macroeconomic factors that influence the risk of financial failure in the aviation industry. Within the parameters of the study, a sample of 11irline firms operating between 2009 and 2019 was analyzed to determine the factors influencing the likelihood of financial failure. The cost of fuel, interest rates, inflation rates, and currency rates were utilized as macroeconomic variables that could have an impact on airline enterprises' ability to meet ends. Financial data and macroeconomic data of the airline companies in the sample were obtained from Thomson Reuters Eikon Datastream. The methodology of the study consists of 2 stages. In the first stage, Altman Z'' Score method is used. Then, panel data analysis method is preferred to reveal the relationship between financial failure and macroeconomic factors. According to the findings of the random effects panel data study, exchange rates and interest rates have a negative impact on financial failure. The results of the changes in interest and exchange rates suggest that governments and airlines should concentrate on policies that will strengthen the aviation sector’s financial viability. To manage these risks more effectively, financial managers must closely examine the effects of rising macroeconomic risk and the corresponding financial failure effects. Airline managers, private and institutional investors should monitor policy uncertainty, assuming that exchange rate uncertainty is a driving force in financial failure. In addition, airline companies should review their hedging strategies against exchange rate risk.
Keywords: Transport Economics; Panel Data Analysis; Financial Failure; Airline financial performance; Altman Z' ' Score; Airline financial risks; Ulaşım Ekonomisi